Exclusive expression of MeCP2 in the nervous system distinguishes between brain and peripheral Rett syndrome-like phenotypes - Ross, Paul D. (Hum Mol Genet, 2016)
Rett syndrome (RTT) is a severe genetic disorder resulting from mutations in the X-linked MECP2 gene. MeCP2 protein is highly expressed in the nervous system and deficiency in the mouse central nervous system alone recapitulates many features of the disorder. This suggests that RTT is primarily a neurological disorder, although the protein is reportedly widely expressed throughout the body. To determine whether aspects of the RTT phenotype that originate in non-neuronal tissues might have been overlooked, we generated mice in which Mecp2 remains at near normal levels in the nervous system, but is severely depleted elsewhere. Comparison of these mice with wild type and globally MeCP2-deficient mice showed that the majority of RTT-associated behavioural, sensorimotor, gait and autonomic (respiratory and cardiac) phenotypes are absent. Specific peripheral phenotypes were observed, however, most notably hypo-activity, exercise fatigue and bone abnormalities. Our results confirm that the brain should be the primary target for potential RTT therapies, but also strongly suggest that some less extreme but clinically significant aspects of the disorder arise independently of defects in the nervous system.